Penggunaan Media Gambar Dalam Keterampilan Berbicara Siswa Pada Pembelajaran Bahasa Indonesia Kelas III Di SDN Tenggilis Mejoyo I Surabaya - Hardiyanti Rukmana (SNHRP, 2022)
The application of serial picture media is a learning that requires students to be active in learning, so that they can solve various practical problems and apply what they learn easily because students see or observe from their own experiences related to the topic being studied. One that was developed in grade 3 and is suitable for applying serial picture media to improve students' speaking skills in Indonesian language learning. The formulation of the problem in this study is "How is the application of serial image media that can improve students' speaking skills in learning Indonesian class III at SDN Tenggilis Mejoyo 1 Surabaya?" "How is the improvement of students' speaking skills learning outcomes after the application of serial picture media in class III at SDN Tenggilis Mejoyo 1 Surabaya?" “The aim is to describe the application of serial picture media that can improve students' speaking skills in class III Indonesian language learning at SDN Tenggilis Mejoyo 1 Surabaya. "Improving students' speaking skills learning outcomes after applying serial image media to Indonesian language learning class III SDN Tenggilis Mejoyo 1 Surabaya". The data collection techniques used were observation, documentation and tests. Data analysis techniques were carried out with the results percentage, and description. Based on the results of the research and discussion, it can be concluded that the application of serial picture media to improve students' speaking skills in learning Indonesian class III SDN Tenggilis Mejoyo 1 Surabaya is categorized B "Good" in addition, the assessment of student learning outcomes in the realm of knowledge (cognitive) obtains a percentage of 83.9 persen categorized as SB “Very Good”.